2020
DOI: 10.1038/s41368-020-0074-x
|View full text |Cite
|
Sign up to set email alerts
|

High expression of ACE2 receptor of 2019-nCoV on the epithelial cells of oral mucosa

Abstract: It has been reported that ACE2 is the main host cell receptor of 2019-nCoV and plays a crucial role in the entry of virus into the cell to cause the final infection. To investigate the potential route of 2019-nCov infection on the mucosa of oral cavity, bulk RNA-seq profiles from two public databases including The Cancer Genome Atlas (TCGA) and Functional Annotation of The Mammalian Genome Cap Analysis of Gene Expression (FANTOM5 CAGE) dataset were collected. RNA-seq profiling data of 13 organ types with para-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
2,309
3
180

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 2,483 publications
(2,646 citation statements)
references
References 24 publications
43
2,309
3
180
Order By: Relevance
“…In this study, we focused on the expression of ACE2 in pancreas and the damage to the pancreas in a proportion of patients with SARS-CoV-2 infection. Although many previous studies have been reported on the expression of ACE2 tissues and organs [15], including bulk RNA-seq and scRNA-seq data, this analysis in the pancreas is still lacking. Firstly, we found ACE2 was mostly expressed in the pancreas of normal people, and it was slightly higher in the pancreas than in the lungs, indicating that when SARS-CoV-2 appeared in the circulation, it might also combine with ACE2 in the pancreas to enter cells and cause pancreatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on the expression of ACE2 in pancreas and the damage to the pancreas in a proportion of patients with SARS-CoV-2 infection. Although many previous studies have been reported on the expression of ACE2 tissues and organs [15], including bulk RNA-seq and scRNA-seq data, this analysis in the pancreas is still lacking. Firstly, we found ACE2 was mostly expressed in the pancreas of normal people, and it was slightly higher in the pancreas than in the lungs, indicating that when SARS-CoV-2 appeared in the circulation, it might also combine with ACE2 in the pancreas to enter cells and cause pancreatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…In supporting the process of entry of the virus into the host cell, SARS-CoV2 binds to the ACE2 receiver that is highly expressed in the lower respiratory tract such as type II alveolar cells (AT2) of the lungs, upper esophagus and stratified epithelial cells, and other cells such as absorptive enterocytes from the ileum and colon, cholangiocytes, myocardial cells, kidney proximal tubule cells, and bladder urothelial cells [14]. Therefore, patients who are infected with this virus not only experience respiratory problems such as pneumonia leading to Acute Respiratory Distress Syndrome (ARDS), but also experience disorders of heart, kidneys, and digestive tract.…”
Section: Figurementioning
confidence: 99%
“…Lymphocytes express the coronavirus receptor ACE2 and may be a direct target of viruses. 9 (2) The virus might directly destroy lymphatic organs. Acute lymphocyte decline might be related to lymphocytic dysfunction, and the direct damage of novel coronavirus virus to organs such as thymus and spleen cannot be ruled out.…”
Section: Analysis Of Possible Reasons For Lymphopenia In Covid-19mentioning
confidence: 99%